Does the development of financial system influence the level of inflation? : A critical survey (Journal of Academic Finance, 2023)
Purpose: The objective of this paper is to examine the impact of financial development on inflation in the Economic and Monetary Community of Central Africa.Method: We use a system GMM as an empirical strategy, using data from the BEAC and WDI databases over the period 1996–2022.Results: The main results of this study show that despite the low level of inflation observed in the Economic and Monetary Community of Central Africa, the credit risk associated with the provision of credit increases inflation. This increase in inflation reduces the performance of the financial sector.Originality of the article: The originality of this article lies in the fact that the central bank must consider financial development as a tool of prudential analysis, which makes it possible to increase the effectiveness of the fight against inflation while improving the performance of the financial sector. This study also shows that financial development is a determinant of inflation.
Keywords: Financial system; inflation; GMM system; performance; spillovers